PENERAPAN MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KEMMPUAN PEMECAHAN MASALAH DI SEKOLAH DASAR - Sagita, Helvina; Fadhilaturrahmi; Marta, Rusdial; Nurhaswinda; Mufarizuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low ability to solve mathematical problems in class V students at SD Negeri 013 Kumantan with a total of 10 students, 3 female students and 7 male students. This research aims to improve problem solving abilities using the Missouri Mathematics Project (MMP) learning model based on local wisdom with material on fraction calculation operations in class V of SD Negeri 013 Kumantan, Kec. Bangkinang City for the 2024/2025 academic year. The research method used is classroom action research (PTK) which is carried out in 2 cycles consisting of two meetings each cycle, has 4 stages, namely planning, implementation, observation and reflection. Data collection techniques use test, observation and documentation techniques. The results of the research showed that in cycle 1 of meeting I, the average student's mathematical problem solving ability (54.2) was in the very low category with a classical completeness percentage of 40%. At meeting II, mathematical problem solving ability increased to (66.9) in the poor category with classical completeness of 60%, in cycle 2 of meeting I increased to average (73.5) in the sufficient category with classical completeness of 80%, then at meeting II in cycle 2 increased again to an average (82.8) in the good category with classical completeness of 80%. Based on the data obtained, it was concluded that by implementing the Missouri Mathematics Project (MMP) learning model, it could improve the mathematical problem solving abilities of fifth grade students at SD Negeri 013 Kumantan.